Parental perspectives on the decision-making process on transport mode choice in adolescents: a qualitative study with mothers and fathers - Tristram, Clara; Reimers, Anne K.; Renninger, Denise; Beck, Franziska; Demetriou, Yolanda; Marzi, Isabel (Frontiers in Psychology, 2023)
Objective The present study aims to understand the familial decision-making process on transport mode choice in adolescents with a focus on the parental perspective within this process. Background Active travel contributes to adolescents’ overall physical activity and its positive health effects. Based on the social-learning theory, especially parents are assigned a central role for adolescents’ travel behavior. The aim of the present study was to examine how parents are involved in the decision-making process on transport mode choice in adolescents. Method The study is part of the cross-sectional mixed-methods ARRIVE study which includes semi-structured interviews with mothers (n = 12) and fathers (n = 7) of 11- to 14-year-old German adolescents. The interviews focused on travel behavior in adolescents and the decision-making process on transport mode choice from the parental perspective. All interviews were analyzed inductively using Thematic Analysis. Results Our study revealed that parents do not primarily decide for or against active travel in adolescents, but are mostly involved in the decision-making process, especially in case of a deviation from the main transport mode. Different forms of parental involvement in the decision-making process were identified. Some parents acted as main decision makers which is the highest form of involvement while others gave their children complete freedom of choose a transport mode for themselves. These parents accepted their child’s choice fully which shows a low involvement in the decision-making process. Conclusion The results provide a deeper understanding of the familial decision-making process on travel behavior in adolescents. The results indicate an occasionally parental involvement in the decision-making process on the mainly used transport mode by adolescents, and that mothers and fathers are always involved when deviating from the main mode. Implications Further research should investigate changes in travel behavior from childhood to young adulthood to understand long-term travel decisions in families. Due to the findings that parents are often involved in the decision-making process on transport mode choice and that they mainly reported safety concerns as barriers to their children’s active travel, further research should focus especially on the social and physical environment of adolescents.